Ideals of the semigroup of ultrafilters of a topological group - Protasov, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We construct two new series of closed left ideals of the semigroup \(τ \) of ultrafilters of a topological group (G, τ). The first series gives a disjunctive decomposition of τ-absorbing ultrafilters. Under certain restrictions on the topology of the group (G, τ), the second series gives a disjunctive decomposition of the semigroup of free ultrafilters. For a nondiscrete metrizable topological group (G, τ), we construct a large free subsemigroup of the semigroup \(τ \) .